Konstruksi Realitas Pemberitaan Kebijakan Vaksinasi Berbayar Di Portal Berita Online - Yona Voria Janesia (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
This study aims to determine the framing of the news regarding the paid vaccination policy or “Vaksin Gotong Royong (VRG)” in Republika Online and Tempo.co. This research is a qualitative research with a constructionist paradigm. The research method used is framing analysis by Robert N. Entman. The framing of Republika Online and Tempo.co news is analyzed through four framing elements, which are problem definition, determining the cause of the problem, making moral decisions, and emphasizing problem solving. The result shows that Republika Online and Tempo.co construct the issue of paid vaccination policy with different framing. Republika Online constructed a paid vaccination policy as a strategic and rational effort to deal with Covid-19. Meanwhile, Tempo.co framed the issue of the paid vaccination policy as a polemic that drew a lot of criticism and rejection. The discourse strategies used by the two media can be observed through the way journalists choose diction, writing headlines, selecting sources, and the body of the news as a whole.